Comparison of treatment persistence, adherence, and risk of exacerbation in patients with COPD treated with single-inhaler versus multiple-inhaler triple therapy: A prospective observational study in China - Lin, Ling; Liu, Cong; Cheng, Wei; Song, Qing; Zeng, Yuqin; Li, Xin; Deng, Dingding; Liu, Dan; Chen, Yan; Cai, Shan; Chen, Ping (Frontiers in Pharmacology, 2023)
Aim: This study sought to compare treatment persistence, adherence, and risk of exacerbation among patients with COPD treated with single-inhaler triple therapy (SITT) and multiple-inhaler triple therapy (MITT) in the Chinese population. Methods: This was a multicenter, prospective observational study. Patients with COPD from ten hospitals in Hunan and Guangxi provinces in China were recruited from 1 January 2020 to 31 November 2021 for the study and were followed up for one year. Treatment persistence, adherence, and exacerbation rates during the 12-month follow-up were analyzed in COPD patients treated with SITT and MITT. Results: A total of 1,328 patients were enrolled for final analysis, including 535 (40.3%) patients treated with SITT and 793 (59.7%) treated with MITT. Of these patients, the mean age was 64.9 years and most patients were men. The mean CAT score was 15.2 ± 7.1, and the median (IQR) FEV1% was 54.4 (31.2). The SITT group had a higher mean CAT score, more patients with mMRC >1, and lower mean FEV1% and FEV1/FVC than the MITT patients. Moreover, the proportion of patients with ≥1 exacerbation in the previous year was higher in the SITT cohort. SITT patients had, compared to MITT patients, a higher proportion of adherence (proportion of days covered, PDC) ≥0.8 (86.5% vs. 79.8%; p = 0.006), higher treatment persistence [HR: 1.676 (1.356–2.071), p < 0.001], lower risk of moderate-to-severe exacerbation [HR: 0.729 (0.593–0.898), p = 0.003], and severe exacerbation [HR: 0.675 (0.515–0.875), p = 0.003], as well as reduced all-cause mortality risk [HR: 0.475 (0.237-0.952), p = 0.036] during the 12-month follow-up. Persistence was related to fewer future exacerbations and mortality than non-persistence in the SITT and MITT groups. Conclusion: Patients with COPD treated with SITT showed improved treatment persistence and adherence, as well as a reduction in the risk of moderate-to-severe exacerbation, severe exacerbation, and mortality compared to patients treated with MITT in the Chinese population. Clinical Trial Registration: https://www.chictr.org.cn/, identifier ChiCTR-POC-17010431.